Vocabulary of Tools in Navoi's Works - X. L. Maxammadiev (Researchparks Publishing, 2021)
It is well known that the tools of labor date back to the primitive times of mankind. Throughout his development, man has created the tools of labor necessary for life, reflecting his material interests. They, like man him, have evolved over time. Many of these tools have been an integral part of a person’s entire life. Everything that a person uses has a specific name in terms of its content, purpose, and function. The history of these lexical units, their place in the Uzbek language dictionary, they have reached us through ancient written sources, most of which are used in the modern Uzbek language in full or in part.